Cross-platform mobile application for electromagnetic analysis - Lim, DeAndre Hai Jie (Nanyang Technological University, 2024)
This report presents the development of a cross-platform mobile application designed for electromagnetic analysis. The application aims to provide a user-friendly interface for calculating and visualising electric and magnetic field intensities. The motivation behind this project is the importance of understanding and accurately calculating these field intensities in various scientific and engineering domains. The report begins with a literature review on electric field intensity and magnetic field intensity. The project design section includes the application's sitemap and blueprint. The report then details the implementation of various features, such as the home page, field intensity calculations for different shapes, input formatting, rounding numbers, and animation of steps. The conclusions highlight the significance of the project and suggest future enhancements, including enhanced visualisation with 3D graphing, integration of Z-axis calculations, comprehensive animation implementation, and expanded electromagnetic coverage. The report concludes by reflecting on the attainment of learning outcomes. The application's development aims to address the need for practical and accessible learning resources in the digitalised era and facilitate self-directed education. Through its step-by-step solutions and user-friendly interface, the application provides learners with a tool to enhance their understanding of electric and magnetic fields and their mathematical intricacies.